Buddha's office : the ancient art of waking up while working well - Zigmond, Dan (Running Press, 2019)
Without setting foot in an office, Buddha knew that helping people work right was essential to helping them find their path to awakening. Now more than ever, we need Buddha's guidance. Too many of us are working long hours, dealing with difficult bosses, high-maintenance coworkers, and non-stop stress. We need someone to help remind us that there is a better way. With Buddha's wisdom at the core of every chapter, Buddha's Office will help you learn how to stop taking shortcuts and pay more attention, care for yourself and others, deal with distractions, and incorporate Buddha's ageless instructions into our modern working life. It's time to wake up and start working in a more enlightened way. One that is right for you, right for our health, right for your sanity, and right for the world.